Assessment of natural radioactivity and radiological impacts in several beaches of Kadikoy, Istanbul - Gunay, Osman (SPRINGER, 2024)
Natural radioactivity (226Ra, 232Th, and 40K) concentrations were determined in sand samples collected from various beaches in Kadikoy-Istanbul (Turkey) at 12 sampling point for the evaluation of radiological parameters such as radiological equivalent activity and excess lifetime cancer risk. The activity concentrations of 226Ra, 232Th, and 40K were found to range between 21.08 and 49.19 Bqkg-1, 20.51-49.92 Bqkg-1, and 173.70-554.16 Bqkg-1, respectively. The selection of Istanbul as the study area is based on its high population density, indicating an increased vulnerability to potential negative effects of radiation exposure.
Keywords: Gamma-ray spectrometry; Annual effective dose; Natural radiation; Beach pollution; Chemistry; Nuclear Science & Technology